An adverse outcome pathway for cigarette smoke-mediated oxidative stress in plaque formation - Makena, Patrudu; Haswell, Linsey E.; McEwan, Michael; Keyser, Brian M.; Smart, David E.; Leverette, Robert; Jordan, Kristen; Breheny, Damien; Baxter-Wright, Sarah (Frontiers in Toxicology, 2025)
Adverse outcome pathways (AOPs) have been developed as a risk assessment tool for regulatory applications. These AOPs describe a logical mechanistic sequence of events, starting with a Molecular Initiating Event (MIE), and ultimately leading to a disease outcome via a series of Key Events (KE). The AOP framework provides a system to make predictions and assessments while reducing the need for in vivo assessment. In the absence of epidemiological evidence, assessment of the health effects of a product, chemical or therapy on the progression of atherosclerosis would necessitate long-term animal exposure studies such as the use of the Apolipoprotein E deficient mouse. We followed Organisation for Economic Co-operation and Development (OECD) guidelines to formulate and propose an AOP for atherosclerotic plaque progression, collating the evidence by which cigarette smoke-induced oxidative stress forms a MIE. The downstream pathway includes multiple KEs including the upregulation of proinflammatory mediators, nitric oxide depletion, and endothelial dysfunction. Alterations in these KEs can lead to plaque formation and progression in cardiovascular disease and increase the risk of morbidity and mortality. Identifying preclinical endpoints and clinical biomarkers associated with these KEs provides a framework for in vitro and clinical data, supporting a mechanistic narrative for regulatory assessment. The application of this pathway provides a powerful alternative to animal models through developing preclinical assays and biomarkers for the assessment of atherosclerosis progression risk.